Pengaruh Budaya Organisasi, Kepuasan Kerja, dan Komitmen Organisasi Terhadap Turnover Intentions (Studi Pada Karyawan Tetap Generasi Milenial di Jabodetabek) - Swastiti, Pradinta Ignatia; Pracoyo, Antyo; Harun, Paulina; Wardani, Deni (Jurnal Keuangan dan Perbankan, 2024)
Indonesia started to entering the era of a bonus demographic in 2012 and predicted its peak occurred in 2035. Demographic if a bonus is used by well, expected to bring change in the thing in Indonesia economy. And supporting role the biggest contributor to the move the bonus demographic is a generation Y or in this study called by generation millennial. But there is the phenomenon of generation millennial is that they will move the work in a short period. Therefore, the purpose of the research is analysing the influence of cultural organization, job satisfaction, and organization commitment to the turnover intentions with a study of permanent workers in greater Jakarta millennial generation. This study shares a questionnaire that is used as the primary data and uncultivated using analysis SEM Amos. Research shows that the directly cultural organizations have a positive influence significantly to job satisfaction, cultural organizations have a positive influence significantly to the organization commitment, cultural organization devoid turnover significantly affect the intentions, job satisfaction having negative influence significantly to turnover intentions, and commitment of the organization have negative influence significantly to turnover intentions. In addition, as for the result of research indirectly, that cultures the organization have significantly affect the turnover intentions through job satisfaction, and cultural organization devoid significantly affect the turnover intentions through the organization commitment.